New pharmacological treatments used in psoriasis: integrative review (Research, Society and Development, 2021)
Psoriasis is a chronic, non-communicable disease that can cause acute pain and disfigurement to the patient, with pharmacological therapy as a satisfactory alternative with the use of retinoids, immunosuppressants and immunobiologicals that provide a great impact on the quality of life of patients, who constantly seek better forms of therapies that demonstrate effective results in controlling the disease. Thus, the article sought to describe the new treatment approaches for psoriasis available in the pharmaceutical market. The research was characterized by being an integrative literature review with data collection in the Lilacs, Medline and Scielo databases, according to the inclusion and exclusion criteria, from a total of 197 articles, 16 were selected to compose the analysis. As a result, there was an application of systemic therapy, with a combination of phototherapy with methotrexate, acitretin, cyclosporine, and biological drugs such as ixequizumab, guselcumab, secukinumab, adalimumab, infliximab, in addition to those for their children. With the study, it is possible to identify which drugs can act in the treatment of psoriasis, such as naltrexone, rottlerin, in addition to the use of an aerosol of calcipotriol and betamethasone dipropionate, and therapy techniques with microinfusion and iontophoresis for the treatment. The possibilities for treating the disease are mainly in the use of drugs, for patients, the main barriers are accessibility, medication usage, and adverse effects that contribute to advances in the remission of the disease.